A semi-metal hydroxide material and its preparation method and application
By preparing semi-metal hydroxide materials with high conductivity and catalytic activity, the problems of expensive traditional precious metal catalysts and poor conductivity of layered bimetal hydroxides are solved, which significantly reduces the overpotential of hydrogen production by electrolytic water and improves the electrolytic water Catalytic properties.
Patent Information
- Application Number
- CN202310916099.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-07-24
AI Technical Summary
Traditional precious metal catalysts have excellent performance but are expensive in the process of electrolyzing hydrogen production, which limits the application of large-scale production of electrolyzed water. The layered bimetallic hydroxide materials have poor electrical conductivity, which limits the improvement of electrocatalytic activity.
Using a preparation method of semi-metal hydroxide material, by dropping the solution of Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O and Mn(NO3)2 in deionized water Mixed with NaOH and Na2CO3 solutions, stirring, washing and ultrasonic dispersion, NaBH4 solution was added to prepare a layered hydroxide material with high conductivity and catalytic activity.
The overpotential of the electrocatalytic reaction is significantly reduced, the energy efficiency of hydrogen production by electrolyzing water is improved, the conductivity of the material is improved by two orders of magnitude, and its performance is better than that of traditional hydroxides and precious metal RuO2 materials.
Smart Images

Figure CN116903054B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nanomaterials and electrochemical technology, and in particular to a preparation method of a semi-metallic layered hydroxide and its electrochemical application. The material can be widely used in the field of water electrolysis catalysts. Background Art
[0002] With the excessive consumption of traditional fossil energy, people are in urgent need of developing a green, sustainable and environmentally friendly energy system. Hydrogen energy, as a carbon-free energy source, has high heat and clean and environmentally friendly reaction products, and is receiving widespread attention. Hydrogen can be prepared in different ways. It can be produced from industrial byproducts or fossil energy. The energy consumption of the reaction process is large and the product purity is low. The purity of hydrogen obtained by water electrolysis hydrogen production technology can be as high as 99.999%, and the preparation process is green and environmentally friendly, which is an ideal way to produce hydrogen. However, the overpotential of the water electrolysis reaction is large, and it is necessary to use electrocatalysts to reduce the activation energy of the reaction process to improve the energy conversion efficiency of electrocatalytic hydrogen production. Traditional precious metal catalysts such as Pt, IrO2, RuO2 and other precious metal electrocatalysts have excellent performance, but they are expensive and not conducive to large-scale application. Therefore, the development and search for low-cost, catalytically excellent non-precious metal material electrocatalysts has become the key to large-scale production and application of water electrolysis. Hydroxide materials, especially layered double hydroxides (LDH), have unique properties such as high specific surface area and adjustable metal element ratio, and are widely used in the field of nanocatalysis. Among them, LDH composed of elements such as Ni and Fe has good intrinsic activity, low cost and abundant reserves, and is considered to be one of the ideal alternative materials for precious metal catalysts for water electrolysis. However, this material has problems such as poor conductivity, which limits the improvement of the material's electrocatalytic intrinsic activity. Summary of the invention
[0003] The present invention provides a semi-metallic hydroxide material and a preparation method thereof. The synthesis process is simple and the operation cycle is short. The prepared material has excellent electrocatalytic performance, effectively reduces the overpotential of the water electrolysis reaction, and improves the energy efficiency of hydrogen production by water electrolysis.
[0004] A method for preparing a semi-metal hydroxide material comprises the following steps:
[0005] S1. Weigh a certain amount of Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O and Mn(NO3)2 solutions respectively, and dissolve them all in deionized water to obtain solution A;
[0006] S2, respectively dissolving NaOH and Na2CO3 in deionized water to obtain solution B;
[0007] S3, adding equal volumes of solution A and solution B to deionized water at a certain drop rate to obtain a dilution, and stirring, washing and drying the dilution in sequence to obtain an intermediate product;
[0008] S4. After ultrasonically dispersing the intermediate product in deionized water to obtain a dispersion, NaBH4 solution is slowly added dropwise to the dispersion. After ultrasonic treatment, centrifugal washing and drying are performed in sequence to obtain a semi-metallic hydroxide material.
[0009] Furthermore, in S1, in solution A, the concentration of Ni(NO3)2·6H2O is 0.7-0.8 mol·L -1 , Fe(NO3)3·9H2O concentration is 0.2~0.3mol·L -1 , Co(NO3)2·6H2O concentration is 0.02~0.03mol·L -1 , Mn(NO3)2 concentration is 0.02~0.03mol·L -1 .
[0010] Furthermore, in S2, in solution B, the concentration of NaOH is 1.5-2.0 mol·L -1 , the concentration of Na2CO3 is 0.5-1.0 mol·L -1 .
[0011] Furthermore, at a drop rate of 20 to 40 mL min -1 ;
[0012] The stirring speed is 500-800 rpm min -1 The stirring process includes stirring at 60-80°C for 1 hour, then transferring to 5-10°C and continuing stirring for 7-10 hours;
[0013] The washing treatment is to use ionized water and ethanol to wash three times;
[0014] The drying temperature is 70-80°C and the drying time is 24 hours or more.
[0015] Furthermore, in S4, the concentration of the intermediate product in the dispersion is 5 to 10 mg·mL -1 .
[0016] Furthermore, in S4, the concentration of the NaBH4 solution is 1-3 mol·L -1 .
[0017] Furthermore, in S4, the centrifugal speed condition is 6000-8000 rpm·min -1, the centrifugation time is set to 5 to 10 minutes;
[0018] The washing treatment is to use ionized water and ethanol to wash three times;
[0019] The drying temperature is 70-80°C and the drying time is 24 hours or more.
[0020] The semi-metal hydroxide material is prepared by the above-mentioned method for preparing the semi-metal hydroxide material.
[0021] Furthermore, the material is a layered hydroxide structure, which is composed of two-dimensional hydroxide nanosheets, and the thickness of the nanosheets is 0.7nm to 70nm.
[0022] Application of the above semi-metal hydroxide materials in the preparation of electrodes.
[0023] The beneficial effects of the present invention are as follows: the semi-metallic hydroxide prepared by the present invention can be used as a catalytic active material for water electrolysis with high conductivity and high catalytic activity. After being doped and constructed with oxygen vacancies, the material can still maintain a layered structure. At the same time, the layer thickness of the sample is adjustable within the range of 0.7nm to 70nm. The metal elements are evenly distributed in the material, and its conductivity is improved by two orders of magnitude compared with traditional hydroxide materials. When the material is used in the field of water electrolysis catalysis, the overpotential of the electrocatalytic reaction can be significantly reduced, indicating that the electrochemical performance of the material is significantly better than that of traditional hydroxides and precious metal RuO2 materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a transmission electron microscope image of the semiconductor hydroxide of Comparative Example 1 of the present invention;
[0025] Figure 2 is an LSV curve diagram of the semi-metal semiconductor hydroxide of Comparative Example 1 of the present invention;
[0026] Figure 3 is a transmission electron micrograph of the semi-metal hydroxide of Example 1 of the present invention;
[0027] Figure 4 is a curve diagram showing the change in resistivity of the semi-metal hydroxide of Example 1 of the present invention with respect to temperature;
[0028] Figure 5 is a comparison chart of the room temperature resistivity of the semiconductor hydroxide of Comparative Example 1 of the present invention and the semi-metallic hydroxide of Example 1;
[0029] Figure 6 is an LSV curve diagram of the semi-metal hydroxide of Example 1 of the present invention; DETAILED DESCRIPTION
[0030] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0031] A method for preparing a semi-metal hydroxide material of the present invention comprises the following steps:
[0032] S1. Weigh a certain amount of Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O and Mn(NO3)2 solution respectively, and dissolve them all in deionized water to obtain solution A. In terms of the amount of substance, Ni(NO3)2·6H2O:Fe(NO3)2·9H2O:Co(NO3)2·6H2O:Mn(NO3)2=29:9:1:1, and in solution A, the concentration of Ni(NO3)2·6H2O is 0.7-0.8 mol·L -1 , Fe(NO3)3·9H2O concentration is 0.2~0.3mol·L -1 , Co(NO3)2·6H2O concentration is 0.02~0.03mol·L -1 , Mn(NO3)2 concentration is 0.02~0.03mol·L -1 ;
[0033] S2. Dissolve NaOH and Na2CO3 in deionized water to obtain solution B. In solution B, the concentration of NaOH is 1.5-2.0 mol·L -1 , the concentration of Na2CO3 is 0.5~1.0mol·L -1 ;
[0034] S3, adding equal volumes of solution A and solution B to deionized water at a certain drop rate, and then stirring, washing and drying in sequence to obtain an intermediate product; wherein the drop rate is 20-40 mL min -1 ; The stirring speed is 500~800rpm min -1 The stirring process includes stirring at 60-80°C for 1 hour in an oil bath, and then transferring to a constant temperature cold bath at 0-10°C for further stirring for 7-10 hours; washing treatment includes washing three times with deionized water and ethanol; drying treatment includes drying at 70-80°C in a vacuum drying oven for 24 hours;
[0035] It should be noted that the deionized water in this step plays a diluting role, and is used to dilute the concentration of each reaction salt substance in solution A and solution B to 0.25-0.4 times the corresponding concentration, such as the concentration of Ni(NO3)2·6H2O from 0.7 to 0.8 mol·L -1Dilute to 0.175~0.2mol·L -1 -0.28~0.32mol·L -1 On the other hand, it is to control the reaction concentration of each reaction salt in solution A and solution B to achieve the purpose of reducing the initial reaction concentration, so that the particles of the prepared semi-metal hydroxide are as small as possible, thereby preparing a uniform product.
[0036] S4. After ultrasonically dispersing the intermediate product in deionized water to obtain a dispersion, NaBH4 solution is slowly added dropwise to the dispersion. After ultrasonic treatment, the dispersion is washed with a centrifuge at a certain speed, and deionized water and ethanol are used for centrifugal washing for more than three times during the centrifugal process. Then, the dispersion is placed in a vacuum drying oven at 70-80°C for drying for more than 24 hours to obtain a semi-metallic hydroxide material, wherein the concentration of the intermediate product in the dispersion is 5-10 mg·mL -1 The NaBH4 solution is prepared by rapidly dissolving sodium borohydride in deionized water at low temperature and ultrasonically to form a solution with a concentration of 1-3 mol·L -1 The uniform solution of NaBH4 solution added to the dispersion is not limited; the ultrasonic treatment time is 2h, and the centrifugal speed is 6000-8000rpm·min -1 , the centrifugation time is set to 5 to 10 minutes.
[0037] <Comparative Example 1>
[0038] A method for preparing a nickel-iron hydroxide material comprises the following steps:
[0039] S1. Weigh 9.30 g Ni(NO3)2·6H2O and 4.30 g Fe(NO3)3·9H2O and dissolve them in 40 mL deionized water to obtain solution A.
[0040] S2, dissolving 2.73 g NaOH and 2.26 g Na2CO3 in 40 mL water to obtain solution B;
[0041] S3, 40 mL of solution A and 40 mL of solution B were mixed at 40 mL min -1 The solution was slowly added dropwise into 40 mL of deionized water using a syringe pump at a dropping rate. During the dropping process, the solution was kept in an oil bath at 60°C and stirred continuously for 1 hour. The pH of the solution was kept at 8.5. The solution was transferred to a cold bath at 10°C and stirred for 7 hours. The obtained sample was then fully washed three times with deionized water and ethanol, and fully dried in a drying oven at 80°C to obtain a brown powder product, namely nickel iron hydroxide.
[0042] Preparation of electrode sheets: 5 mg of nickel iron hydroxide and 2 mg of Super P were weighed into a small beaker, and 1 mL of ethanol solution and 5 μL of Nafion solution were added. The mixed slurry was fully ultrasonicated for 15 min, and then the obtained sample was dropped on carbon paper and the electrocatalytic performance was tested.
[0043] The transmission electron microscopy image of the nickel iron hydroxide prepared in this comparative example is as follows Figure 1 As shown in the figure, the material is a two-dimensional nanosheet structure with a layer thickness of about 2.46nm.
[0044] The electrode sheet was used for water electrolysis test and found that Figure 2 The LSV curves show that the nickel-iron semiconductor hydroxide has a -2 The overpotential at a current density of 310 mV.
[0045] <Example 1>
[0046] A method for preparing a semi-metal hydroxide material comprises the following steps:
[0047] S1. Weigh 9.0 g Ni(NO3)2·6H2O, 3.9 g Fe(NO3)3·9H2O, and 0.31 g Co(NO3)2·6H2O respectively, and use a pipette to measure 248.1 μL of 50% Mn(NO3)2 solution, and dissolve them all in 40 mL deionized water to obtain solution A;
[0048] S2, dissolving 2.73 g NaOH and 2.26 g Na2CO3 in 40 mL water to obtain solution B;
[0049] S3, 40mL solution A and 40mL solution B were mixed at 40mL min -1 The dropping rate was set at 40 mL of deionized water (dilution ratio was 0.4 times) with a syringe pump. During the dropping process, the solution was kept in an oil bath at 60 °C and stirred continuously for 1 h. After the dropping was complete, the pH of the solution was kept at 8.5 and the solution was transferred to a cold bath at 10 °C and stirred for 7 h. The stirring speed was 500 rpm min. -1 The obtained sample was then washed three times with deionized water and ethanol, and then dried in a drying oven at 80°C to obtain a brown powdery intermediate product;
[0050] S4, weigh 100 mg of the intermediate product and disperse it in 20 mL of deionized water by ultrasonic, then weigh 2.27 g of NaBH4 and disperse it in 20 mL of deionized water (concentration is 3 mol L -1), and fully mixed under low temperature ultrasonic conditions, the prepared NaBH4 solution was slowly added dropwise thereto, and after complete addition, it was fully ultrasonicated in an ultrasonic machine for 2 hours, and then centrifuged at 6000 rpm min -1 After centrifugation for 10 minutes, the sample was centrifugally washed three times with deionized water and ethanol, and then placed in a drying oven at 80° C. and fully dried for 24 hours to obtain a semi-metallic hydroxide material.
[0051] Preparation of electrode sheets: Weigh 5 mg of semi-metal hydroxide material and 2 mg of Super P into a small beaker, add 1 mL of ethanol solution, and add 5 μL of Nafion solution. Ultrasonicate the mixed slurry for 15 min, then drop the obtained sample on carbon paper and test the electrocatalytic performance.
[0052] The transmission electron microscope image of the semi-metal hydroxide obtained in the embodiment is obtained, and the result is as follows: Figure 3 As shown in the figure, the microstructure of the semi-metal hydroxide is a nanosheet structure. Figure 1 In comparison, the thickness of the nanosheets of the material did not change significantly and was about 2.66nm. Figure 4 As shown in the figure, the resistivity curve of the material tested by the four-probe conductivity tester shows that the resistivity of the material first decreases and then increases with the increase of temperature, which represents the transformation of the material from the semiconductor state to the semi-metal state. Figure 5 As shown, the resistivity of the nickel iron hydroxide prepared in Comparative Example 1 and the semi-metal hydroxide material prepared in this example at room temperature (25°C) is compared. It is found that the resistivity of the prepared semi-metal hydroxide at room temperature is two orders of magnitude lower than that of the nickel iron hydroxide, indicating that the conductivity of the material is significantly improved. A slurry of a certain concentration is prepared and dripped onto carbon paper to test its water electrolysis performance. Figure 6 As shown, it was found that the material -2 At a current density of , the overpotential of the electrode is only 234 mV, which is much better than the commercial RuO2 electrocatalyst. Compared with the electrocatalytic material prepared in Comparative Example 1, its overpotential is reduced by 76 mV. The above results show that the semi-metallic hydroxide prepared by this embodiment has excellent conductivity, and the electrocatalytic activity of the material is significantly improved compared with the original nickel iron hydroxide.
[0053] <Example 2>
[0054] A method for preparing a semi-metal hydroxide material comprises the following steps:
[0055] S1. Weigh 9.0 g Ni(NO3)2·6H2O, 3.9 g Fe(NO3)3·9H2O, and 0.31 g Co(NO3)2·6H2O respectively, and use a pipette to measure 248.1 μL of 50% Mn(NO3)2 solution, and dissolve them all in 40 mL deionized water to obtain solution A;
[0056] S2, dissolving 4.12 g NaOH and 2.26 g Na2CO3 in 40 mL water to obtain solution B;
[0057] S3, 40 mL of solution A and 40 mL of solution B were mixed at 40 mL min -1 The solution was slowly added into 40 mL of deionized water using a syringe pump at a dropping rate. During the dropping process, the solution was kept in an oil bath at 60°C and stirred continuously. After the dropping was complete, the pH of the solution was kept at 8.5. The solution was transferred to a cold bath at 10°C and stirred for 7 hours. The obtained sample was then fully washed three times with deionized water and ethanol, and fully dried in a drying oven at 80°C to obtain a brown powder intermediate product.
[0058] S4. Weigh 100 mg of brown powdery intermediate product and disperse it in 20 mL of deionized water by ultrasonic. Then weigh 2.27 g of NaBH4 and disperse it in 20 mL of deionized water and mix thoroughly. Slowly drop the prepared NaBH4 solution into the solution. After the addition is complete, ultrasonicate it in an ultrasonic machine for 2 h and centrifuge it at 6000 rpm min. -1 After centrifugation for 10 minutes, the sample was centrifugally washed three times with deionized water and ethanol, and then placed in a drying oven at 80° C. and fully dried for 24 hours to obtain a semi-metallic hydroxide material.
[0059] Preparation of electrode sheets: Weigh 5 mg of semi-metal hydroxide material and 2 mg of Super P into a small beaker, add 1 mL of ethanol solution, and add 5 μL of Nafion solution. Ultrasonicate the mixed slurry for 15 min, then drop the obtained sample on carbon paper and test the electrocatalytic performance.
[0060] In this example, the content of NaOH added was changed, and the electrocatalytic performance of the prepared semi-metal hydroxide material electrode was tested. It was found that the material -2 At a current density of , the overpotential of the electrode is 274 mV. Compared with Example 1, its water electrolysis performance is reduced.
[0061] <Example 3>
[0062] A method for preparing a semi-metal hydroxide material comprises the following steps:
[0063] S1. Weigh 9.0 g Ni(NO3)2·6H2O, 3.9 g Fe(NO3)3·9H2O, and 0.31 g Co(NO3)2·6H2O respectively, and use a pipette to measure 248.1 μL of 50% Mn(NO3)2 solution, and dissolve them all in 40 mL deionized water to obtain solution A;
[0064] S2, dissolving 2.73 g NaOH and 2.26 g Na2CO3 in 40 mL water to obtain solution B;
[0065] S3, 40 mL of solution A and 40 mL of solution B were mixed at 40 mL min -1 The solution was slowly added into 40 mL of deionized water using a syringe pump at a dropping rate. During the dropping process, the solution was kept in an oil bath at 60°C and stirred continuously. After the dropping was complete, the pH of the solution was kept at 8.5. The solution was transferred to a cold bath at 10°C and stirred for 7 hours. The obtained sample was then fully washed three times with deionized water and ethanol, and fully dried in a drying oven at 80°C to obtain a brown powder intermediate product.
[0066] S4. Weigh 100 mg of brown powdery intermediate product and disperse it in 20 mL of deionized water by ultrasonic. Then weigh 0.7566 g of NaBH4 and disperse it in 20 mL of deionized water and mix thoroughly. Slowly drop the prepared NaBH4 solution into the solution. After the addition is complete, ultrasonicate it in an ultrasonic machine for 2 h and centrifuge it at 6000 rpm min. -1 After centrifugation for 10 minutes, the sample was centrifugally washed three times with deionized water and ethanol, and then placed in a drying oven at 80° C. and fully dried for 24 hours to obtain a semi-metallic hydroxide material.
[0067] Preparation of electrode sheets: Weigh 5 mg of semi-metal hydroxide material and 2 mg of Super P into a small beaker, add 1 mL of ethanol solution, and add 5 μL of Nafion solution. Ultrasonicate the mixed slurry for 15 min, then drop the obtained sample on carbon paper and test the electrocatalytic performance.
[0068] In Example 3, the content of NaBH4 added (i.e., the concentration of the NaBH4 solution) was changed, and the electrocatalytic performance of the prepared semi-metallic hydroxide material electrode was tested. It was found that the material -2 At a current density of , the overpotential of the electrode is 284 mV. Compared with Example 1, its water electrolysis performance is reduced.
[0069] <Example 4>
[0070] A method for preparing a semi-metal hydroxide material comprises the following steps:
[0071] S1. Weigh 8.14 g Ni(NO3)2·6H2O, 3.28 g Fe(NO3)3·9H2O, and 0.23 g Co(NO3)2·6H2O respectively, and use a pipette to measure 298.1 μL of 50% Mn(NO3)2 solution, and dissolve them all in 40 mL deionized water to obtain solution A;
[0072] S2, dissolving 2.4 g NaOH and 2.12 g Na2CO3 in 40 mL water to obtain solution B;
[0073] S3, 40 mL of solution A and 40 mL of solution B were mixed at 40 mL min -1 The solution was slowly added into 40 mL of deionized water using a syringe pump at a dropping rate. During the dropping process, the solution was kept in an oil bath at 60°C and stirred continuously. After the dropping was complete, the pH of the solution was kept at 8.5. The solution was transferred to a cold bath at 10°C and stirred for 7 hours. The obtained sample was then fully washed three times with deionized water and ethanol, and fully dried in a drying oven at 80°C to obtain a brown powder intermediate product.
[0074] S4. Weigh 100 mg of brown powdery intermediate product and disperse it in 20 mL of deionized water by ultrasonic. Then weigh 2.27 g of NaBH4 and disperse it in 20 mL of deionized water and mix thoroughly. Slowly drop the prepared NaBH4 solution into the solution. After the addition is complete, ultrasonicate it in an ultrasonic machine for 2 h and centrifuge it at 6000 rpm min. -1 After centrifugation for 10 minutes, the sample was centrifugally washed three times with deionized water and ethanol, and then placed in a drying oven at 80° C. and fully dried for 24 hours to obtain a semi-metallic hydroxide material.
[0075] Preparation of electrode sheets: Weigh 5 mg of semi-metal hydroxide material and 2 mg of Super P into a small beaker, add 1 mL of ethanol solution, and add 5 μL of Nafion solution. Ultrasonicate the mixed slurry for 15 min, then drop the obtained sample on carbon paper and test the electrocatalytic performance.
[0076] In this example, the concentration of metal salt in S1 and the concentration of NaOH and Na2CO3 in S2 were changed, and the electrocatalytic performance of the prepared semi-metal hydroxide material electrode was tested. It was found that the material -2 At a current density of , the overpotential of the electrode is 288 mV. Compared with Example 1, its water electrolysis performance is reduced.
[0077] <Example 5>
[0078] A method for preparing a semi-metal hydroxide material comprises the following steps:
[0079] S1. Weigh 9.3 g Ni(NO3)2·6H2O, 4.29 g Fe(NO3)3·9H2O, and 0.349 g Co(NO3)2·6H2O respectively, and use a pipette to measure 506.7 μL of 50% Mn(NO3)2 solution, and dissolve them all in 40 mL deionized water to obtain solution A;
[0080] S2, dissolving 3.2 g NaOH and 4.239 g Na2CO3 in 40 mL water to obtain solution B;
[0081] S3. Mix equal volumes of 40 mL of solution A and 40 mL of solution B at 40 mL min. -1 The solution was slowly added into 40 mL of deionized water using a syringe pump at a dropping rate. During the dropping process, the solution was kept in an oil bath at 60°C and stirred continuously. After the dropping was complete, the pH of the solution was kept at 8.5. The solution was transferred to a cold bath at 10°C and stirred for 7 hours. The obtained sample was then fully washed three times with deionized water and ethanol, and fully dried in a drying oven at 80°C to obtain a brown powder intermediate product.
[0082] S4. Weigh 100 mg of brown powdery intermediate product and disperse it in 20 mL of deionized water by ultrasonic. Then weigh 2.27 g of NaBH4 and disperse it in 20 mL of deionized water and mix thoroughly. Slowly drop the prepared NaBH4 solution into the solution. After the addition is complete, ultrasonicate it in an ultrasonic machine for 2 h and centrifuge it at 6000 rpm min. -1 After centrifugation for 10 minutes, the sample was centrifugally washed three times with deionized water and ethanol, and then placed in a drying oven at 80° C. and fully dried for 24 hours to obtain a semi-metallic hydroxide material.
[0083] Preparation of electrode sheets: Weigh 5 mg of semi-metal hydroxide material and 2 mg of Super P into a small beaker, add 1 mL of ethanol solution, and add 5 μL of Nafion solution. Ultrasonicate the mixed slurry for 15 min, then drop the obtained sample on carbon paper and test the electrocatalytic performance.
[0084] In this example, the concentration of metal salt in S1 and the concentration of NaOH and Na2CO3 in S2 were changed, and the electrocatalytic performance of the prepared semi-metal hydroxide material electrode was tested. It was found that the material -2 At a current density of , the overpotential of the electrode is 299 mV. Compared with Example 1, its water electrolysis performance is reduced.
[0085] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.
[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a semi-metal hydroxide material, characterized in that: The following steps are involved: S1. Weigh a certain amount of Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O and Mn(NO3)2 solutions respectively and dissolve them all in deionized water to obtain solution A; the concentration of Ni(NO3)2·6H2O is 0.7~0.8 mol·L -1 , Fe(NO3)3·9H2O concentration is 0.2~0.3 mol·L -1 , Co(NO3)2·6H2O concentration is 0.02~0.03 mol·L -1 , Mn(NO3)2 concentration is 0.02~0.03 mol·L -1 ; S2. Dissolve NaOH and Na2CO3 in deionized water to obtain solution B; the concentration of NaOH is 1.5-2.0 mol·L -1 , the concentration of Na2CO3 is 0.5-1.0 mol·L -1 ; S3, adding equal volumes of solution A and solution B to deionized water at a certain drop rate to obtain a dilution, and stirring, washing and drying the dilution in sequence to obtain an intermediate product; S4. After ultrasonically dispersing the intermediate product in deionized water to obtain a dispersion, a NaBH4 solution is slowly added dropwise to the dispersion. After ultrasonic treatment, centrifugal washing and drying are performed in sequence to obtain a semi-metallic hydroxide material; the concentration of the NaBH4 solution is 1-3 mol·L -1 .
2. The method for preparing a semi-metal hydroxide material according to claim 1, characterized in that: In S3, the drip rate is 20-40 mL min -1 ; The stirring speed is 500~800 rpm min -1 The stirring process includes stirring at 60-80 °C for 1 h, then transferring to 5-10 °C and continuing stirring for 7-10 h; The washing treatment is to use ionized water and ethanol to wash three times; The drying temperature is 70-80 °C and the drying time is more than 24 h.
3. The method for preparing the semi-metal hydroxide material according to claim 1, characterized in that: In S4, the concentration of the intermediate product in the dispersion is 5-10 mg·mL -1 .
4. The method for preparing a semi-metal hydroxide material according to claim 1, characterized in that: In S4, the centrifugal speed condition is 6000~8000 rpm·min -1 , the centrifugation time was set to 5-10 min; The washing treatment is to use ionized water and ethanol to wash three times; The drying temperature is 70-80 °C and the drying time is more than 24 h.
5. The semi-metal hydroxide material obtained by the method for preparing the semi-metal hydroxide material according to any one of claims 1 to 4.
6. The semi-metal hydroxide material according to claim 5, characterized in that The material is a layered hydroxide structure composed of two-dimensional hydroxide nanosheets with a thickness of 0.7 nm to 70 nm.
7. Use of the semi-metal hydroxide material according to claim 5 in preparing electrodes.